1979
DOI: 10.1093/bja/51.4.313
|View full text |Cite
|
Sign up to set email alerts
|

cOMPARISON OF FLUNITRAZEPAM AND DIAZEPAM FOR ORAL PREMEDICATION IN OLDER CHILDREN

Abstract: A double-blind trial was conducted of two benzodiazepines, flunitrazepam and diazepam, given orally to 142 children (30 kg in weight or heavier) undergoing routine surgery. Flunitrazepam was associated with greater sedation before operation and less vomiting after operation than diazepam. Flunitrazepam caused a greater frequency of amnesia for the periods of induction and immediately after operation. Plasma concentrations were measured in 65 children and were found to be significantly greater in those children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Benzodiazepines were compared to each other in 17 studies [7,18,27,29,31,39,41,43,53,54,55,57,59,61,62,64,67]. Six of these studies compared different benzodiazepines [18,39,43,53,57,62], six compared dosages [29,31,41,55,61,64], one compared the time of administration [7], and 4 compared routes [27,54,59,67].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzodiazepines were compared to each other in 17 studies [7,18,27,29,31,39,41,43,53,54,55,57,59,61,62,64,67]. Six of these studies compared different benzodiazepines [18,39,43,53,57,62], six compared dosages [29,31,41,55,61,64], one compared the time of administration [7], and 4 compared routes [27,54,59,67].…”
Section: Resultsmentioning
confidence: 99%
“…Six of these studies compared different benzodiazepines [18,39,43,53,57,62], six compared dosages [29,31,41,55,61,64], one compared the time of administration [7], and 4 compared routes [27,54,59,67]. Only four studies found significant differences among groups: in one study, intravenous midazolam was more likely than intravenous diazepam to produce amnesia for pain, but there was no difference with regard for amnesia of events [39].…”
Section: Resultsmentioning
confidence: 99%
“…In children (Boyd and Manford, 1973;Richardson and Manford, 1979;Beeby and Morgan Hughes, 1980) it is now accepted that the administration of premedication by mouth is safe, effective and preferred by the patient (Doughty, 1959). Lorazepam has been studied in children (Mundeleer, 1980) and appeared satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in children have been limited to its use as a premedication. It appears that flunitrazepam is an effective premedicant in both adults and children (Kanto et al 1979b;Lindgren et al 1979;Richardson & Manford 1979).…”
Section: Use In Pregnancy and In Childrenmentioning
confidence: 99%